Valorization of Agricultural Waste from Piggeries in Residential Areas to Promote Sustainable Production - Kodani, Samuel (Geography, Earth Science and Environment: Research Highlights Vol. 1, 2024)
Piggeries are a quick way of generating an income in agriculture. Pigs multiply fast and can be used to generate an income within a short space of time, bringing in better livelihoods for the farmers and their families. Apart from the bright side of hog raising, there are some policy challenges in economic, environmental, health and social dimensions for sustainable agriculture. There are places where piggeries are located within residential areas hence need to consider their implication on the wellbeing of the people and their environment. An evaluation of opinions of various inhabitants of Seke Communal lands, in Mashonaland East province of Zimbabwe indicated that 70% of the population do not support piggery projects to be sited within the vicinity of homesteads. This population understood and resented the social and environmental implications of piggery waste and wastewater within their community. When proximate analysis was carried out on pig waste. It was noted to possess high levels of phosphates and nitrates amongst other nutrients. These were noted to be beneficial in crops when handled sustainably in promoting green production. On the other side, when handled otherwise, the same elements may pollute the environment with serious consequences. It was noted that splitting the waste into solid and liquid reduced the foul smell peculiar to piggeries. Using the waste management hierarchy priorities, piggery waste nutrients and wastewater recycling were recommended as better options for production system sustainability and environmental protection. It was noted that the solid waste could be composted or processed into organic fertilizers. Irrigation suitability tests were used to recommend the liquid for prior treatment before field applications through irrigation in promoting the circular economy. The same liquid could be edified and used in liquid fertilizer manufacturing. This study demonstrated the need for proper piggery waste management especially when the piggeries are located amongst various homesteads and also adequate regulatory enforcement. It was also noted that there is a need to keep updating statutory instruments in line with current scientific findings pertaining to the implications of piggery waste and wastewater on current environmental demands.